2012
DOI: 10.1051/0004-6361/201118288
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic temperatures toward X1/X2 orbit interceptions regions and giant molecular loops in the Galactic center region

Abstract: Context. It is well known that the kinetic temperatures, T kin , of the molecular clouds in the Galactic center region are higher than in typical disk clouds. However, the T kin of the molecular complexes found at higher latitudes towards the giant molecular loops in the central region of the Galaxy is so far unknown. The gas of these high-latitude molecular clouds (hereafter referred to as "halo clouds") is located in a region where the gas in the disk may interact with the gas in the halo in the Galactic cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
1
15
1
Order By: Relevance
“…A.3). Thus, we decided to use 10 K which is consistent with our estimations in Riquelme et al (2013) for CS, and with the discussion in Section 5.1.…”
Section: 1mentioning
confidence: 82%
“…A.3). Thus, we decided to use 10 K which is consistent with our estimations in Riquelme et al (2013) for CS, and with the discussion in Section 5.1.…”
Section: 1mentioning
confidence: 82%
“…6 of Hüttemeister et al (1993), who make the same plot for NH 3 (4, 4) and (5, 5). Riquelme et al (2013) also found no correlation using NH 3 over a similar range of velocity dispersions. While there is no clear correlation between velocity dispersion and temperature, most data points fall within a range that is consistent with turbulent heating if the appropriate size scale is selected; see Fig.…”
Section: Gas Heating and Thermal Balancementioning
confidence: 86%
“…6.2 of Lucas 2015) because the gravitational force F g ∝ m/r 2 increases with increasing galactocentric radius for the observed CMZ mass profile, where m ∝ r 2.2 (Launhardt et al 2002; see Kruijssen et al 2015 for the measurement of the power-law slope in the radial interval of about 10 to 100 pc that is of interest here). The clouds are further compressed by the high external pressure; gas temperatures of typically 50 to 100 K in CMZ clouds (Güsten et al 1981;Hüttemeister et al 1993;Ao et al 2013;Mills & Morris 2013;Ott et al 2014;Ginsburg et al 2016; also see Riquelme et al 2010aRiquelme et al , 2012 imply H 2 densities 10 4 cm −3 to balance 2 the aforementioned pressure of 10 6 to 7 K cm −3 . Finally, the strong and widespread SiO emission tracing shocks (Martín-Pintado et al 1997;Hüttemeister et al 1998;Riquelme et al 2010b), prevalence of molecules likely ejected from grain surfaces via shocks 1 The classical reviews by, for example, Güsten (1989) and Morris & Serabyn (1996) state that clouds are subject to disruptive shear.…”
Section: Introductionmentioning
confidence: 99%